Sistem Informasi WIP (Work In Process) Berbasis Web Menggunakan Metode Waterfall - Hary Alfarizi; Abdul Halim Anshor; Edora (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Inventory is stock, or stored material or goods that are used for a specific purpose. Meanwhile, WIP, also known as work in process, is an inventory of semi-finished goods. So, if it is concluded that inventory work in process is the inventory of goods that have entered the production stage but have not been completed until the end of becoming a finished product, PT Hexpharm Jaya is a pharmaceutical company that produces various types of medicines. PT Hexpharm Jaya has a WIP (Work In Progress) inventory room for storage of Masa Siap Cetak (MSC) and Masa Siap Strip (MSS) products. But currently, the system that runs in the WIP inventory room still uses a paper format (logbook), so it often faces problems in the process of work activities. So a computerized system is a solution that is relevant to the existing problems. This research was conducted to overcome these problems. This information system development technique uses the waterfall method because of its structured and sequential nature, which suits the need to develop a system with clear and well-defined phases. The stages in the waterfall method include requirements analysis, system design, implementation, testing, and maintenance. This web-based WIP Information System, can produce success in inventory management, improve operational efficiency, increase visibility over production status, speed up workflow, and also increase company productivity. And it is hoped that this research can make a significant contribution to inventory management practices by introducing the web-based WIP Information System that has been developed.